NAFTA 2.0: a way forward for the investment chapter - Mélida Hodgson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
The contentious NAFTA negotiations have yet to produce a concrete proposal for the investment chapter. The Trans-Pacific Partnership investment chapter, an improvement over NAFTA, can be enhanced to create a modern chapter that balances national interests. This Perspective offers some ideas of how to get there.
Keywords: 330